RPL26 variants: a rare cause of Diamond-Blackfan anemia syndrome with multiple congenital anomalies at the forefront - Vanlerberghe, Clémence; Frénois, Frédéric; Smol, Thomas; Jourdain, Anne-Sophie; Escande, Fabienne; Aït-Yahya, Emilie; Aldeeri, Abdulrahman A.; Yu, Timothy W.; Cormier-Daire, Valérie; Ghoumid, Jamal; Jacob, Maureen; Newbury-Ecob, Ruth; et al. (Genetics in medicine, 2024)
Purpose - Diamond-Blackfan anemia syndrome (DBS) is a rare congenital disorder originally characterized by bone marrow failure with or without various congenital anomalies. At least 24 genes are implicated, the vast majority encoding for ribosomal proteins. RPL26 (ribosomal protein L26) is an emerging candidate (DBA11, MIM#614900). We aim to further delineate this rare condition. - Methods - Patients carrying heterozygous RPL26 variants were recruited. In one of them, erythroid proliferation and differentiation from peripheral blood CD34+ cells were studied by flow cytometry, and RPL26 expression by quantitative reverse transcription polymerase chain reaction and immunoblotting. - Results - We report on 8 affected patients from 4 families. Detailed phenotyping reveals that RPL26 is mainly associated with multiple congenital anomalies (particularly radial ray anomalies), albeit with variable expression. Mandibulofacial dysostosis and neural tube defects are potential features in DBA11, expanding the growing list of DBS abnormalities. In 1 individual, we showed that RPL26 haploinsufficiency was responsible for subclinical impairment in erythroid proliferation and enucleation. The absence of hematological involvement in 4 adults from this series contributes to the mounting evidence that bone marrow failure is not universally central to all DBS genes. - Conclusion - We confirm RPL26 as a DBS gene and expand the phenotypic spectrum of the gene and the disease.